PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA POWERPOINT INTERAKTIF TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA KELAS IV SD - Larasati, Fala Risky; Purwasi, Lucy Asri; Maharani, Tidi (LP4MK STKIP PGRI Lubuklinggau, 2024)
This study aims to determine the ability to solve mathematical problems after the application of the problem based learning (PBL) model assisted by interactive powerpoint of fourth grade students of SD Negeri 59 Lubuklinggau is significantly categorized as good. This type of research is in the form of a quasi-experiment carried out without a comparison group. The population in this study were all fourth grade students of SD Negeri 59 Lubuklinggau, totaling 38 students. The sample was class IV.A students who were taken randomly. Data collection was taken using the test technique in the form of descriptions. The data analysis technique used the t-test with a significance level of α = 0.05. Based on the results of the data analysis, it can be concluded that the ability to solve mathematical problems of students after the application of the problem based learning (PBL) model assisted by interactive powerpoint of fourth grade students of SD Negeri 59 Lubuklinggau is significantly categorized as good. The average value of students' mathematical problem solving abilities after being given treatment was 70. The percentage of students with good and very good categories was 83.33%. Keywords: Problem Based Learning Model, Problem Solving Ability